¿Qué significa en el ordenamiento español el derecho a «vivir con dignidad el proceso de la muerte»? - Rey Martínez, Fernando (2012)
What does «the right to live the process of dying with dignity» mean in Spanish law?Different recent regulatory developments in Spanish legal system are analyzed in this article concerning person’s rights at the end of its life. In particular, the author attempts to explain the enigmatic sense of the new expression “the right to live the process of dying with dignity” and beyond its current configuration as a “legal” right—more than a constitutional one—. Also attempts to catalogue it as a new fundamental right.